Considering the Aspects of Life during the Fetal Life and Their function in Blood Money - Dr. Seyyed Abolghsem Hosseini (آموزه‌‌های فقه مدني)
here is a conception in religious texts in the title of “to give life to” fetus and it is considered as the standard of paying blood money in its different stages. This conception makes somebody to understand that there is no life in fetus until four month and after it the life will be given to it. In accordance to Islamic texts and the facts of embryology, there is life in all stages of fetal life. After four month and after completing heart and brain, a new phenomenon which is called in Islamic text “Uncreated spirit of God” will be existed in him. By coming into existence, fetus becomes completed and if someone aborts it, he should pay one thousand Dinar (a complete blood money).